Gluconic Acid from Biomass Fast Pyrolysis Oils: Specialty Chemicals from the Thermochemical Conversion of Biomass. Issue 11 (9th September 2014) - Santhanaraj, Daniel; Rover, Marjorie R.; Resasco, Daniel E.; Brown, Robert C.; Crossley, Steven
Abstract Fast pyrolysis of biomass to produce a bio‐oil followed by catalytic upgrading is a widely studied approach for the potential production of fuels from biomass. Because of the complexity of the bio‐oil, most upgrading strategies focus on removing oxygen from the entire mixture to produce fuels. Here we report a novel method for the production of the specialty chemical, gluconic acid, from the pyrolysis of biomass. Through a combination of sequential condensation of pyrolysis vapors and water extraction, a solution rich in levoglucosan is obtained that accounts for over 30 % of the carbon in the bio‐oil produced from red oak. A simple filtration step yields a stream of high‐purity levoglucosan. This stream of levoglucosan is then hydrolyzed and partially oxidized to yield gluconic acid with high purity and selectivity. This combination of cost‐effective pyrolysis coupled with simple separation and upgrading could enable a variety of new product markets for chemicals from biomass.